Dissolution and the Consequent Surface Enrichment of Platinum in Pt–Cu Binary Alloys under Potential Cycling. Issue 10 (17th June 2020) - Ooi, Azusa; Tada, Eiji; Nishikata, Atsushi
Abstract : In this study, electrochemistry was combined with mass spectroscopy and surface analysis to investigate the selective dissolution of Cu and the consequent surface enrichment of Pt in Pt–Cu binary alloys. Two different compositions of Pt–50at% Cu (Pt–50Cu) and Pt–75at% Cu (Pt–75Cu) underwent potential cycling. Cu from both alloys was selectively dissolved, although trivial Pt dissolution occurred, causing the subsequent formation of a Pt-enriched layer on the alloys' surfaces. The morphology of the layer was quite different between the two alloys. The Pt-enriched layer formed on the Pt–50Cu surface was extremely thin and compact, further suppressing Cu dissolution from the alloy in the later stage of potential cycling. The Pt-enriched layer formed on the Pt–75Cu surface contained numerous pits, mainly because a lot of Cu was dissolved from Pt–75Cu during potential cycling. Thus, Cu continued to dissolve from the bottom of the pits at the later stage, causing the thickness of the Pt-enriched layer to gradually grow with an increase in the cycle number. The correlation between Pt and Cu dissolution and surface morphological changes of Pt–Cu alloys was discussed.